1984
DOI: 10.1128/aac.25.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in duration of common colds by zinc gluconate lozenges in a double-blind study

Abstract: As a possible treatment for common colds, we tested zinc gluconate lozenges in a double-blind, placebocontrolled, clinical trial. One 23-mg zinc lozenge or matched placebo was dissolved in the mouth every 2 wakeful h after an initial double dose. After 7 days, 86% of 37 zinc-treated subjects were asymptomatic, compared with only 46% of 28 placebo-treated subjects (P = 0.0005). Side effects or complaints were usually minor and consisted mainly of objectionable taste and mouth irritation. Zinc lozenges shortened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
182
2
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 16 publications
5
182
2
1
Order By: Relevance
“…Even with the recognition that placebo in the present study was not entirely devoid of activity, there was a significant (P< 0.025) reduction in the severity of symptoms in the ZGG treatment group compared with placebo at day 7; day 7 has been commonly used for comparison in other published studies that include duration and symptom severity data. 1,2,15 The effects observed in the present study indicate that there may be a 1 -2 day 'window of opportunity' for treatment with ZGG before the common cold takes hold. It could be determined from further studies whether cold symptoms would last an even shorter time if ZGG treatment were begun on the day of symptom onset.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Even with the recognition that placebo in the present study was not entirely devoid of activity, there was a significant (P< 0.025) reduction in the severity of symptoms in the ZGG treatment group compared with placebo at day 7; day 7 has been commonly used for comparison in other published studies that include duration and symptom severity data. 1,2,15 The effects observed in the present study indicate that there may be a 1 -2 day 'window of opportunity' for treatment with ZGG before the common cold takes hold. It could be determined from further studies whether cold symptoms would last an even shorter time if ZGG treatment were begun on the day of symptom onset.…”
Section: Discussionmentioning
confidence: 57%
“…This is further suggested by another study, which found a significant reduction of symptoms when a non-chelating formulation was used. 7 The present study was carried out to test the hypothesis that pleasant-tasting ZGG lozenges that release 93% of the ionic zinc into saliva may produce similar efficacy to that originally reported by Eby et al 1 …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The immuno logical mechanisms of action of zinc that they cited appear correct and it is also true that they are of a delayed nature. However, they probably cannot alone account for the rapid therapeutic action of strong zinc lozenges in aborting colds as was first reported by Eby et al [2] and elsewhere. The fact that the first observation of the rapid action of zinc lozenges against colds occurred in a child with T-cell leukemia and with no functional immune system due to chemotherapy is a good indicator that more is involved [2].…”
mentioning
confidence: 90%
“…However, they probably cannot alone account for the rapid therapeutic action of strong zinc lozenges in aborting colds as was first reported by Eby et al [2] and elsewhere. The fact that the first observation of the rapid action of zinc lozenges against colds occurred in a child with T-cell leukemia and with no functional immune system due to chemotherapy is a good indicator that more is involved [2]. There is a local mechanism of action: the mouth-nose biologically closed electric circuit (BCEC) [3,4], which appears to explain the rapid therapeutic response to zinc lozenges.…”
mentioning
confidence: 90%